2020
DOI: 10.1177/0164027520917059
|View full text |Cite
|
Sign up to set email alerts
|

Life-Course Religious Attendance and Cognitive Functioning in Later Life

Abstract: Although several studies suggest that religious attendance is associated with better cognitive functioning in later life, researchers have generally failed to connect with any established life-course perspectives or theories of cognitive aging. Building on previous work, we examine the effects of life-course religious attendance on a range of cognitive functioning outcomes. We employ data from the religious life histories module of the 2016 Health and Retirement Study, a subsample of 516 adults aged 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 44 publications
5
36
1
2
Order By: Relevance
“…We found statistically nonsignificant associations between R/S and breast cancer screening among Albertan women enrolled in ATP. Our work aligns with recent publications showing equivocal results for religion as a protective factor for health (e.g., Hill et al (2020) and their research on religious attendance and cognitive function in later life). Future research should include broader measures of R/S and move from cross-sectional to longitudinal data analyses ( Suh et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…We found statistically nonsignificant associations between R/S and breast cancer screening among Albertan women enrolled in ATP. Our work aligns with recent publications showing equivocal results for religion as a protective factor for health (e.g., Hill et al (2020) and their research on religious attendance and cognitive function in later life). Future research should include broader measures of R/S and move from cross-sectional to longitudinal data analyses ( Suh et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…A clear advantage of the NLSY data is it includes prospective measurements of religious attendance between 1979 and 2000 (although religious attendance is available only in these two waves). These prospective measurements are most closely aligned with life course approaches but are rare in actual practice (Hill et al 2020). This is preferable to retrospective self-reports, which are subject to recall bias (R. D. Hayward, Maselko, and Meador 2012).…”
Section: Methodsmentioning
confidence: 99%
“…This type of engagement evokes hope, encourages a healthy lifestyle and alleviates symptoms of depression, one of the causes of cognitive deficits. However, a study involving adults aged 65+ years, showed that subjects reporting significant religious engagement, understood as highly frequent attendance in services, exhibited poorer working memory and lower general cognitive performance than the subjects attending religious functions less frequently (Hill, Carr, Burdette, Dowd-Arrow, 2020).…”
Section: Spirituality and Intangible Valuesmentioning
confidence: 99%